The Evaluation of Red Cell Distribution Width in Chronic Hemodialysis Patients - Hikmet Tekce; Buket Kin Tekce; Gulali Aktas; Mehmet Tanrisev; Mustafa Sit (International Journal of Nephrology)
Background. Red cell distribution width (RDW) has been used as a marker of iron deficiency; however, it is accepted as a marker of cardiovascular survival. We aimed to study RDW levels in hemodialysis (HD) patients and the association between RDW and inflammatory, nutritional, and volume markers. Methods. We included 296 HD patients with sufficient iron storage and without anemia or hypervolemia. We grouped patients into four groups according to clinical parameters, albumin, and C-reactive protein (CRP). Results. The lowest RDW levels were found in group 1 (13.2%). Although RDW of group 2 was higher than that of group 1, it was still in normal range (14.7% versus 13.2%, P=0.028). RDW levels of groups 3 (17.8%) and 4 (18.5%) were significantly higher than those of groups 1 and 2 and above normal range. A positive correlation was detected between RDW and HD duration, interdialytic weight gain (IDWG), serum phosphate, and CRP levels and a negative correlation was detected with serum albumin. HD duration, CRP, IDWG, and serum albumin have been found as independent predictors of RDW elevation. Conclusions. Results of the present study reflect adverse effects of inflammation, malnutrition, and excess IDWG on RDW elevation in an HD study cohort with sufficient iron storage and without anemia and hypervolemia.